Monitoring SARS-CoV-2 decontamination by dry heat and ultraviolet treatment with a swine coronavirus as a surrogate. Issue 1 (March 2021) - Singh, G.; Jorgenson, J.; Pringle, T.; Nelson, T.; Ramamoorthy, S.
Summary: The critical need for reliable methods to validate decontamination protocols for personal protective equipment (PPE) for re-use during the SARS-CoV-2 pandemic is limited by the need for specialized containment facilities to handle the virus. Hence, we have herein validated the use of a swine coronavirus as a surrogate, and tested the effectiveness of dry heat and ultraviolet (UV) rays for PPE decontamination. Exposure of experimentally contaminated N95 masks and hospital gowns to 60°C for 20 min, and UVC at 1800 mJ/cm 2 resulted in a 4-log reduction and inactivation of the surrogate virus. This study provides a novel alternative to validate PPE reprocessing methods.